Effect of ADRB2 (adrenergic receptor β2) gene polymorphisms on the occurrence of asthma and on the response to nebulized salbutamol in South Indian patients with bronchial asthma. (14th September 2015) - Shah, Neel Jayesh; Vinod Kumar, Saka; Gurusamy, Umamaheswaran; Annan Sudarsan, Arun Kumar; Shewade, Deepak Gopal
Abstract: Introduction : Genetic mutations in the β2 receptor could alter its functioning and the response to β2 agonists. The study was done to find out the effect of two commonly occurring polymorphisms-Arg16Gly and Gln27Glu, on cause of asthma and on response to nebulized salbutamol in South Indian subjects of asthma. Methods : After baseline measurements of Forced Expiratory Volume in 1st second (FEV1 ), Forced Vital Capacity (FVC) and Peak Expiratory Flow Rate (PEFR), five mg of nebulized salbutamol was administered and spirometry was repeated. The increase in these parameters was calculated and patients were included for genotyping if the percentage increase in FEV1 was ≥12%. The frequencies of these polymorphisms in patients were compared with those of healthy volunteers. Results : 112 patients and 127 healthy volunteers were genotyped. The frequencies of the polymorphisms were found to be similar to previously published Dravidian population frequencies. The frequencies of genotypes in asthmatics were similar to healthy volunteers. The increase in FEV1, FVC and PEFR was similar across various genotypes and haplotypes in both the polymorphisms. The GG-CG haplotype was associated with 3.1 times increased occurrence of asthma ( p value = 0.02). The G allele of the Arg16Gly polymorphism was associated with lower baseline FEV1, FVC and PEFR values, but these were not statistically significant. Conclusion : The Arg16Gly and Gln27Glu polymorphisms do not determine the occurrence of asthma individually, but the GG-CG haplotype is associated with an increased risk of asthma. There is no effect of the genotypes on the response to nebulized salbutamol.